Design of an Accounting System Using Microsoft Excel for the MSME LPK Fernan Indo Jaya - Silvia Rahayu; Anita (Universitas Internasional Batam, 2025)
This project was initiated to help LPK Fernan Indo Jaya, a vocational driving training center that still manages its finances using manual record books. As the institution’s activities grew, this traditional method became increasingly inefficient, and errors occurred easily, reports took a long time to prepare, and important data had a higher risk of being lost. To address these problems, the team developed a simple accounting system using Microsoft Excel that fits the daily operational needs of the institution. The project used a qualitative descriptive approach, where information was gathered through discussions with the owner and administrative staff, direct observation of how transactions were handled, and documentation of the system once it was implemented. The Excel-based system produced from this process includes several connected sheets that make it easier to record income from training services, track expenses, and automatically generate financial reports. The results show that the new system improves accuracy, saves time, and helps the management make more informed decisions. For the students involved, this project also served as a practical learning experience in understanding user needs, designing simple applications, and applying classroom knowledge in real work situations. Overall, the project illustrates how an accessible and user-friendly accounting tool can strengthen financial management for MSMEs and support future development efforts.